Successional trajectories of seed dispersal mode and seed size of canopy tree species in wet tropical forests - Wendt, Amanda L.; Chazdon, Robin L.; Vargas Ramirez, Orlando (Frontiers in Forests and Global Change, 2022)
Despite the critical role of seed dispersal for tree colonization during forest succession in wet tropical forests, successional trajectories of seed dispersal modes are poorly documented at the community level. Overall successional trends in wet tropical forests indicate that, over time, animal-dispersed and large-seeded species increase in relative abundance in woody vegetation, whereas wind-dispersed and small-seeded species decline. Increased abundance of animal-dispersed trees during succession may be attributed to higher rates of seed deposition by animals and higher survival rates of animal-dispersed species with larger seeds (diaspores) compared to wind-dispersed species. We compiled categorical information on seed size (maximum seed length) and dispersal mode (anemochory, autochory, or zoochory) for 240 canopy tree species in six naturally regenerating forests (11–45 years since the abandonment of pasture) and two old-growth forests in lowland wet forests in northeastern Costa Rica. We evaluated dispersal mode and seed size among tree species classified as second growth and old growth specialists, and generalists based on relative abundance data in these plots. Further, we compared long-term trajectories in the dispersal and seed-size profile for 240 species of canopy tree species for seedlings, saplings, and trees ≥5 cm dbh using annual vegetation survey data from 1997 to 2013. Seed size was significantly associated with dispersal mode, which was driven by anemochorous species with intermediate seeds 6 mm to 15 mm and autochorous seeds with large seeds >15 mm. Dispersal modes of canopy tree species exhibited clear directional trajectories, with decreasing relative abundance of anemochory and increasing relative abundance of zoochory. Zoochorous seedlings showed higher survival rates than anemochorous seedlings. Species with seeds ≤ 6 mm decreased in relative abundance through succession, while species with seeds >15 mm increased within seedling and sapling communities. Seedlings with seeds >15 mm showed higher survival rates than smaller seeds in second-growth forests. The study further demonstrates the importance of seed traits, such as dispersal mode and seed size, for community assembly during forest regrowth, and the importance of frugivorous animals in this process. The abundance of animal-dispersed tree species in different size classes can be a useful indicator of the recovery of biodiversity and species interactions during forest succession in wet tropical regions.